Restoring a Burnt Heritage PTPN X Building in Surabaya - Theresia Ratna Darmiwati (Journal of Visual Art and Design, 2015)
The archipelago of Indonesia has lots of historical buildings that were built during the Dutch colonization era, which lasted for approximately 350 years.  In 2011, there were 167 colonial architectural buildings in Surabaya city [1].  Due to their importance to the city as testimony of the history of Surabaya, and are a way to develop heritage tourism in Surabaya, the city government must preserve them.  A thorough research study has been done to support the city government in restoring a heritage building called PT Perkebunan Nusantara X (PTPN X).  It is a state-owned agricultural business office located at Jalan Jembatan Merah, Surabaya, and located among other historical sites. The PTPN X building was burnt down in 2005 with a damage level of about 60%.  In order to be able to build a new one with the original design of its past European architecture and details of its historical relics, the restoration acts require intensive consultations with many people such as the PTPN X employees, academic experts from Institute of Technology Sepuluh Nopember (ITS) and the city's cultural heritage experts who know all about it. In this paper, the approaches and final outcome of the building restoration will be described in greater detail. Keywords: colonial architectural building; heritage building restoration; tourism and education; PTPN X.